Isolation and characterization of Streptomyces spp. from soils - Tan, G.Y.; Ho, C.Y.; Tan, E.L.; Thong, Kwai Lin (Malaysian Society for Molecular Biology and Biotechnology, 2001)
The isolation of forty-eightstrains of actinomycetesfrom eightsoil sampleswas donewith the conventional dilution plate method on Humic acid-vitamin agar (lfVA), Starch Casein agar and Sorenson's agar. FIVAwas found to be the best isolation medium as more strains of actinomycete could be isolated. Based on the aerial mycelium colour scheme, three colour groups were recognised. Representative isolates from each colour group were subjected to macrorestriction analysis with the pulsed-field gel electrophoresis (PFGE). The different coloured strainsexhibitedlowlevelsofsimilariry(Dice coefficient,F<0.50).A cetoneextractsoftheisolateswerescreened on mutant yeastsf or Mitogen-Activated Protein Kinase (MAPK) Kinase and MAPK Phosphatasei nhibitor to find an indirect inhibitor of ras. However, no inhibitor was found but seven isolates exhibited toxic effect towards the yeasts. PFGE analysis of these isolates showed that two of isolateswere identical. From the phenotlpic and genotypic characteristics, the two isolates were shown to be of the same strain.